HOW MANY COOKS DOES IT TAKE TO SPOIL A SOUP?: SAN JUAN COUNTY V. U.S. AND INTERVENTIONS IN R.S. 2477 LAND DISPUTES (Utah Environmental Law Review; Vol 29 No 1 (2009), 2009)
Normal 0 false false false EN-US X-NONE X-NONE /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} Under an 1866 mining statute, many federal and private lands in the West have been burdened by right-of-way claims. Revised Statute 2477 (“R.S. 2477”) was passed during the Civil War era to accommodate western expansion by granting easements over unreserved public lands. When federal policy shifted from expansion to preservation, however, this provision created as many complexities and uncertainties as it did rights-of-way. After several legislative and administrative attempts to resolve these issues, jurisdiction finally fell to federal courts to decide the validity of R.S. 2477 claims. Today, thousands of outstanding claims continue unresolved due to the cost, delay and uncertainty of litigation.